Free surface reconstruction of opaque liquids in microgravity. Part 2: Drop tower campaign. (December 2021) - Romero-Calvo, Á.; Garrone, F.; García-Salcedo, A.J.; Rivoalen, I.; Cano-Gómez, G.; Castro-Hernández, E.; Maggi, F.
Abstract: This paper addresses the operation in microgravity of the surface reconstruction device whose design is detailed in the first part of the manuscript. The system, employed during the drop tower campaign of the UNOOSA DropTES 2019 StELIUM experiment, studies the axisymmetric and lateral oscillations of a ferrofluid solution in microgravity. The free liquid surface is reconstructed in a cylindrical tank and relevant metrics of the magnetic sloshing problem, such as contact angles, hysteresis parameters, natural oscillation frequencies, or damping ratios, are derived. The result is a rich and unique database where several phenomena of scientific and technological interest are reported for the first time. The dependence of the fundamental axisymmetric and lateral modal frequencies with the applied magnetic field is consistent with the literature and past experiments. Although the detection system was designed and built using low-cost hardware, high-quality results are obtained. Highlights: Microgravity measurements from a novel surface reconstruction device are presented. The system successfully reconstructs the movement of a free ferrofluid surface. Relevant metrics of the magnetic sloshing problem are measured for the first time. Modal shapes and frequencies are identified as a function of the magnetic environment.